2019
DOI: 10.1155/2019/3028721
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Experimental Study on Multifactor Conditions for Gas Desorption in Coal

Abstract: The isothermal adsorption experiment of coal is an important method to study the mechanism of coal gas desorption. The orthogonal experiment is used to compare the gas desorption mechanism of coal under multifactor conditions, such as the particle size, temperature, pressure, moisture content, and molding pressure. The sensitivity of five factors was used to conduct regression analysis. The sensitivity and influence degree of five factors on the coal gas desorption capacity were analyzed. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Each recoverable coal seam is judged to be in danger of coal and gas outbursts according to the critical thresholds of four indicators for the identification of outburst-prone coal seams (as shown in Table 1) 24 . After fixed-size sampling of the coal seam, the coal sample is processed and industrially analyzed according to the Proximate Analysis Method of Coal (GB/T212-2008) 25 . The industrial analysis results are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Each recoverable coal seam is judged to be in danger of coal and gas outbursts according to the critical thresholds of four indicators for the identification of outburst-prone coal seams (as shown in Table 1) 24 . After fixed-size sampling of the coal seam, the coal sample is processed and industrially analyzed according to the Proximate Analysis Method of Coal (GB/T212-2008) 25 . The industrial analysis results are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Each coal sample is not less than 1 kg. According to the China Coal Industry Standard [19] to prepare the coal sample for proximate analysis and gas adsorption experiment, the humidification process for coal samples is shown in Figure 3. e data of proximate analysis of coal samples, coal hardiness coefficient, and initial gas diffusion velocity of coal are shown in Table 1.…”
Section: Sample Preparationsmentioning
confidence: 99%
“…Gas desorption of granular coal is the gas transfer process in porous media, and this process is affected by particle size, pressure, temperature, and other factors [12,13]. Wang et al [14] showed that the sensitivity of gas desorption law to particle size, temperature, pressure, moisture content, and forming pressure was pressure > temperature > particle size > moisture content > forming pressure. Qin et al [15] proved that the desorption process of granular coal was inhibited when the desorption environment pressure was higher than the atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%